1998
DOI: 10.2527/1998.7682177x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutritional management, trace mineral supplementation, and norgestomet implant on attainment of puberty in beef heifers.

Abstract: We conducted a study to evaluate the influences of nutritional management, trace mineral supplementation, and exogenous progesterone on attainment of puberty in beef heifers. Heifers (n = 180) were assigned at weaning to blocks and treatments. Treatments included two dietary regimens (corn silage vs pasture + oatlage), trace mineral supplementation, and puberty induction strategy (with or without progestin implant). Heifers that received pasture + oatlage were managed on grass-legume pastures from October 14 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…The present study further showed nutritional restrictions during the prebreeding period clearly affected heifer performance. When nutritionally restricted animals are placed on a higher plane of nutrition, they will subsequently gain BW faster and have a lower feed-to-gain ratio than animals not nutritionally restricted (Fox et al, 1972;Grings et al, 1998;Kelln et al, 2011). However, in the current study, BW differences following the winter development period were present until the first calving period (approximately 10 mo after the development period) and first-calf weaning period (approximately 17 mo after the development period), respectively.…”
Section: Heifer Performancementioning
confidence: 49%
“…The present study further showed nutritional restrictions during the prebreeding period clearly affected heifer performance. When nutritionally restricted animals are placed on a higher plane of nutrition, they will subsequently gain BW faster and have a lower feed-to-gain ratio than animals not nutritionally restricted (Fox et al, 1972;Grings et al, 1998;Kelln et al, 2011). However, in the current study, BW differences following the winter development period were present until the first calving period (approximately 10 mo after the development period) and first-calf weaning period (approximately 17 mo after the development period), respectively.…”
Section: Heifer Performancementioning
confidence: 49%
“…Grings et al (2007) concluded that heifers, when weaned at 140, 190, or 240 d of age, and subsequently developed on either constant or delayed gain management strategies can all achieve similar reproductive success. Furthermore, spring-born heifers, of similar age, weaned on fall pasture then subjected to a period of dry lot confinement had similar attainment of puberty as heifers consuming a corn silage based diet throughout the same time period in the Northern Great Plains, USA (Grings et al, 1998). Clanton et al (1983) concluded that producers have many options to effectively develop replacement heifers as long as necessary body weight (BW; industry standard of 65% of mature BW) that supports reproductive competency is achieved by the start of breeding.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of trace element supplementation on reproduction in controlled experiments have been varied (DiCostanzo et al, 1986;Phillippo et al, 1987;Vaughan et al, 1994). We previously observed no effect of a combined Cu, Zn, and Mn supplement on the number of heifers reaching puberty before the first breeding season (Grings et al, 1998). Diet and animal breed can influence mineral utilization, and we, therefore, wanted to further evaluate mineral supplementation for heifers under different management than that previously studied.…”
Section: Introductionmentioning
confidence: 99%